2012
DOI: 10.1186/1476-4598-11-85
|View full text |Cite
|
Sign up to set email alerts
|

Combined targeting of AKT and mTOR synergistically inhibits proliferation of hepatocellular carcinoma cells

Abstract: BackgroundDue to the frequent dysregulation of the PI3K/AKT/mTOR signaling pathway, mTOR represents a suitable therapeutic target in hepatocellular carcinoma (HCC). However, emerging data from clinical trials of HCC patients indicate that mTOR inhibition by RAD001 (Everolimus) alone has only moderate antitumor efficacy which may be due to the feedback activation of AKT after mTOR inhibition. In this study, we analyzed the effects of dual inhibition of mTOR and AKT on the proliferation of HCC cell lines. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
75
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 49 publications
11
75
0
Order By: Relevance
“…We aimed in investigating the effect of combined Akt and mTOR inhibition on B-pre ALL cells using the novel allosteric, clinically available pan-Akt inhibitor MK-2206. 29 This combination has been demonstrated to be effective in hepatocellular carcinoma cell lines, 53 cholangiocarcinoma cell lines 38 and in an in vivo model of castration-resistant prostate cancer. 54 Moreover, we used a second combination consisting of CCI-779 and GSK 690693.…”
Section: Dual Mtor/akt Inhibition In B-pre All Lm Neri Et Almentioning
confidence: 99%
“…We aimed in investigating the effect of combined Akt and mTOR inhibition on B-pre ALL cells using the novel allosteric, clinically available pan-Akt inhibitor MK-2206. 29 This combination has been demonstrated to be effective in hepatocellular carcinoma cell lines, 53 cholangiocarcinoma cell lines 38 and in an in vivo model of castration-resistant prostate cancer. 54 Moreover, we used a second combination consisting of CCI-779 and GSK 690693.…”
Section: Dual Mtor/akt Inhibition In B-pre All Lm Neri Et Almentioning
confidence: 99%
“…[10][11][12][13][14] In the clinic, combination chemotherapy for breast cancer is widely used, including drugs such as dasatinib and adriamycin, and has shown excellent results.…”
Section: )mentioning
confidence: 99%
“…9) A growing body of literature has also shown that drug combinations have synergistic anti-cancer effects through the inhibition of these targets. [10][11][12][13][14] In the clinic, combination chemotherapy for breast cancer is widely used, including drugs such as dasatinib and adriamycin, and has shown excellent results. 15) The clinical application of combination chemotherapy covers a wide range of treatments and chemotherapy-related antimetabolite drugs combined with anti-tumor drugs have also had a significant impact, for example, the synergistic anticancer effect of a combination of capecitabine and docetaxel in the treatment of metastatic breast cancer.…”
mentioning
confidence: 99%
“…In addition, PAQR3 negatively regulates the transactivation activity of hypoxia-inducible factor 1α (HIF-1α) by inhibiting formation of the HIF-1α/p300 complex and suppressing VEGF transcription, thereby reducing hypoxia-induced VEGF production (12). Furthermore, recent studies have found that PAQR3 is implicated in a set of human cancers, including clear-cell renal cell carcinoma and colorectal cancer (12,13). However, the significance of altered expression of PAQR3 in HCC has not been fully elucidated due to the lack of studies using fresh human tumor samples.…”
Section: Introductionmentioning
confidence: 99%